Reversible Data Hiding Techniques for VQ-Compressed Domain - Nguyễn Thái Sơn (Feng Chia University, 2022)
Data hiding is designed to solve the problem of secure information exchange through networks such as Internet. In that, reversible data hiding is the good technique for recovering original images without any distortion after secret data are extracted from the stego image. This technique continues to attract attention from many researchers. In this thesis, three reversible data hiding schemesare proposed to embed secret data into the VQ and SMVQ compressed image.